Актуальність розробки додатків з вивчення ПДР - Надточій, Д. В. (ХНУРЕ, 2023)
Nowadays, more and more people use smartphones in their daily life in various fields of activity. The topic of the theory of traffic rules was not left out of digitalization, and was taken as a basis for the development of mobile applications. The article examines the urgency of developing an application for the study of traffic laws and their problems.
Keywords: вивчення ПДР; навчання